Indicadores de qualidade física de argissolos sob pastagens no leste e sul de MG - Oliveira, Gilmar Gonçalves de (2015)
This research has been conducted in Lixisols areas in the Eastern and Southern Regions of Mina Gerais with the aim of evaluating the physical quality of the topsoil of this area, basing the results on Water Retention Curves (WRC) and using the secondary native vegetation as a reference. A completely randomized experimental design has been used for this purpose, with 4 management systems (Southern Pastures of Minas, Eastern Pastures of Minas under medium shepherding pressure, Eastern Pastures under High Shepherding pressure and Vegetation) and 3 repetitions, totalizing 12 samples. To obtain the WRC, the samples of soil with preserved structure were prepared and subjected to matric potentials of -4, -6 e -10kPa for suction units and to potentials of -33, - 100, -500 e -1500 kPa for Richards chambers. The attributes indicating the physic quality of the soil were calculated using the WCR: micro and macroporosity, total porosity, water retention capacity and Index S. The soil density (SD) was determined by the volumetric ring method. Under the conditions of the research, the WRC, the SD and the porosity were good indicators of the physical quality of the soil, as the results prevented from concluding that there were any physical alterations in the chosen topsoil in Minas Gerais. The values of SD in the Easter Pastures of Minas possibly indicate soil superficial compression. Nonetheless, the relation between Index S and soil degradation is still in need of better researches, as the sensibility of the said Index in the diagnostic of the structural modifications derived from the use of the soil has not been confirmed.